General dentists knowledge about the emergency management of dental avulsion in Yemen - Nabil M Al-Zubair (Wolters Kluwer Medknow Publications, 2015)
Objective: The objective of this research was to investigate the knowledge of general dentists about the emergency management of dental avulsion in Sana'a, Yemen. Materials and Methods: A questionnaire containing nine questions about emergency management of avulsed teeth was distributed among 416 general dental practitioners working in different private dental hospitals and clinics of Sana'a among them 272 was responded. Results: Among the studied group, (44%) said that an avulsed permanent tooth cannot be replanted. Sixty-eight percent of the responded informed that they use rigid splint for avulsed tooth and 29% said that semi-rigid splint should be used. Conclusion: The results suggest that the level of knowledge on the management of dental avulsion of the general practitioners dentists in Sana'a is inadequate. An education program should be conducted to increase the knowledge of general dentists in the management of traumatic injuries to teeth.